Mathematical model of politomous diagnostical test - Krylovas, Aleksandras; Kosareva, Natalja (Lietuvos matematikos rinkinys, 2010)
The technology of politomous diagnostic operators as general testing tool creation from the empirical data is proposed. Requirements to diagnostic operators are formulated as a system of axioms. Probability distribution of test result and the amount of test information are calculated according to the proposed technique.